Food safety knowledge, attitudes and practices of street food vendors and consumers in Ho Chi Minh city, Vietnam. (December 2016) - Samapundo, S.; Cam Thanh, T.N.; Xhaferi, R.; Devlieghere, F.
Abstract: This study had the major objective of evaluating the food safety knowledge, attitudes and practices of consumers and vendors of street foods in Ho Chi Minh City (MCMC), Vietnam. There were three main surveys performed in this study. A total of 120 consumers and 40 street food vendors from four districts [Binh Thanh (BT), Thu Duc (TD), district 3 (D3) and district 8 (D8)] in HCMC contributed to the study on a voluntary basis. The surveyed consumers had adequate levels of food safety knowledge and attitudes. No significant difference ( p  > 0.05) occurred between the food safety knowledge levels of the consumers on the basis of gender. However, significant differences ( p  < 0.05) occurred on the basis of age, education level, food safety training status and location. In contrast, the street vendors had poor food safety knowledge and attitude levels. No significant differences ( p  > 0.05) were observed in the food safety knowledge levels of the vendors on the basis of gender and age. However, significant differences ( p  < 0.05) were found on the basis of food safety training status and education level. It was also noted that the vast majority (95%) of the vendors had not received any food safety training. With regards to the practices, it was determined that 52.5% of the vending sites were open air stands without any protection from the sun, wind and dust. 52.5% the vending stalls had no direct access to potable water, while 47.5% did not have adequate hand washing facilities and a further 30% lacked proper waste water and food disposal facilities. In addition, 52.5% of the vendors did not separate raw, partially cooked food and cooked food products. These findings highlighted that street food vendors in HCMC generally have poor food handling practices and most are operating under unhygienic conditions. These results should provide the Vietnamese government with even more reasons to increase their current efforts to improve the safety of street foods and food safety awareness of the consumers. Highlights: Food safety knowledge, attitudes, and practices were evaluated in Ho Chi Minh City. 120 consumers and 40 vendors from four different districts volunteered. Consumers had adequate food safety knowledge and attitude levels. The food vendors had poor food safety knowledge and attitude levels. Food vendors in Ho Chi Minh City operate under largely unhygienic conditions.